SCINTIGRAPHIC ILLUSTRATION OF ALIMENTARY TRACT DUPLICATION IN A PATIENT SUSPECTED OF MECKEL’S DIVERTICULUM - A CASE REPORT: Alimentary Tract Duplication - Ali, Col Mujahid Khalid; Mirza, Tariq Mahmood; Dar, Ziagham Salim; Raza, Syed Mehdi (Pakistan Armed Forces Medical Journal, 2013)
Alimentary Canal Duplication (ATD) is a rare developmental anomaly of the gut with reported incidence of 1 in 45001. It may occur anywhere in the gut from thoracic part of esophagus to midgut and hindgut and may involve urinary and genital systems as well2. However, ileum is the most common site accounting for 44% of cases3. These lesions characteristically consist of well developed smooth muscle coat, mucosa originating from any part of the gut and anatomy close to any of the major portions of gastrointestinal tract4. The clinical picture depends upon the site and size of duplication,5 ranging from completely asymptomatic to malena or rectal bleeding and sometimes to severe intestinal obstruction, intussusceptions and volvulus that may prove to be life threatening.